Pericytes regulate VEGF-induced endothelial sprouting through VEGFR1. Issue 1 (December 2017) - Eilken, Hanna; Diéguez-Hurtado, Rodrigo; Schmidt, Inga; Nakayama, Masanori; Jeong, Hyun-Woo; Arf, Hendrik; Adams, Susanne; Ferrara, Napoleone; Adams, Ralf
Abstract Pericytes adhere to the abluminal surface of endothelial tubules and are required for the formation of stable vascular networks. Defective endothelial cell-pericyte interactions are frequently observed in diseases characterized by compromised vascular integrity such as diabetic retinopathy. Many functional properties of pericytes and their exact role in the regulation of angiogenic blood vessel growth remain elusive. Here we show that pericytes promote endothelial sprouting in the postnatal retinal vasculature. Using genetic and pharmacological approaches, we show that the expression of vascular endothelial growth factor receptor 1 (VEGFR1) by pericytes spatially restricts VEGF signalling. Angiogenic defects caused by pericyte depletion are phenocopied by intraocular injection of VEGF-A or pericyte-specific inactivation of the murine gene encoding VEGFR1. Our findings establish that pericytes promote endothelial sprouting, which results in the loss of side branches and the enlargement of vessels when pericyte function is impaired or lost. Pericytes are essential for the development, maintenance and function of vascular networks. Here, Eilken and colleagues show that expression of the decoy receptor VEGFR1 by pericytes spatially restricts VEGF signalling, thus regulating VEGF-induced endothelial cell sprouting in developing tissues.